From Postcolonial Histories to Digital Futures: Rethinking Global Communication in the Global South - Afolabi, Ololade (International Journal of Mass Communication, 2026)
This essay invites scholars of global communication to rethink the field from a broader perspective. It challenges the dominant theoretical traditions that have long shaped research in global communication and argues for greater openness to interdisciplinary approaches capable of fostering a more expansive epistemological framework. By examining global communication through both historical and postcolonial lens, the paper calls for a multidimensional framework in which history and postcolonial experiences are theorized in more rigorous ways for scholars seeking to study communication from a Global South perspective, thereby expanding the analytical relevance and reach of the discipline.